The association between physical activity and mental health status among employees at semenyih eco-venture resort and recreation / Nur Azura Mahmud and Mohammad Adzly Rajli - Mahmud, Nur Azura; Rajli, Mohammad Adzly (Universiti Teknologi MARA, Negeri Sembilan, 2025)
The relationship between physical activity and mental health status has been widely studied, but research focusing on employees in Malaysia remains limited. This study investigates the level of physical activity and mental health status among employees at Semenyih Eco Venture Resort and Recreation. By examining their association, the findings will contribute to workplace wellness strategies and address gaps in local research. This study employed a quantitative, non-experimental design using a purposive sampling approach. A structured questionnaire was administered to 33 employees at Semenyih Eco Venture Resort and Recreation. The International Physical Activity Questionnaire (IPAQ-short form) assessed physical activity levels [1], while the Depression Anxiety and Stress Scale (DASS-21) measured mental health status [2]. Descriptive and inferential statistics were used to analyze physical activity levels, METs/week, and mental health outcomes.